Spectator, enter the paradox in Duras's virtual film L'Homme Atlantique. Issue 1 (2nd January 2021) - Groff, Elizabeth
ABSTRACT: While much of the criticism of director Marguerite Duras's cinema has tended to prioritise sound over image, the writing process over the cinematographic one, this article argues that at every moment, Duras evokes cinema, its components and its material, thus making Duras a cineaste who thinks cinema . To establish this, the author explores the fundamental questions asked by Duras about the medium of cinema in her film L'Homme Atlantique (1981): What is cinema, and what can it do? She first demonstrates how Duras evokes each element of the apparatus: the screen, the cinema theatre room, the celluloid and the individual image unit on the celluloid – the photogram. She then examines Duras's use of the black shot and demonstrates how it is in fact an image and not a negation or absence of image. Finally, she investigates the spectator and the camera, where Duras's spatio-temporal reconfiguration is fully illuminated. The discussion shows that in L'Homme Atlantique, space-time remains in a potential, non-actualised, virtual state.